Pelajar Islam Indonesia Kontribusi Pelajar Islam Indonesia (PII) terhadap Perkembangan Pendidikan dan Dakwah di Tapan dari Tahun 1990 hingga 2006 - Saputra, Yandi Asrida; Putra, Johan Septian (Universitas Negeri Padang, 2024)
This study examines the role of Pelajar Islam Indonesia (PII) in developing Islamic education and proselytization in Tapan, West Sumatra, during the period 1990-2006. The main objective is to understand PII's contribution in strengthening Islamic values among students through religious activities such as Quran study groups, leadership training, and cadre formation. Using historical methods and a qualitative approach, the study collected data from interviews, archival documents, and secondary sources. The analysis stages included heuristics, source criticism, synthesis, and historiographical writing to build a comprehensive narrative. The main findings indicate that PII played an essential role in filling gaps in religious education in Tapan, particularly for young people who needed a platform for Islamic character building. Despite various challenges, including the single principle of Pancasila policy imposed during the New Order era, PII managed to sustain its presence through adaptive strategies, such as using alternative names for its activities and employing flexible approaches that remained consistent with Islamic values. PII's role in Tapan has had a significant social impact, fostering young cadres with strong religious understanding who can contribute as community leaders. The study concludes that PII in Tapan has successfully fulfilled its mission as an Islamic educational organization, consistently reinforcing Islamic values amid political constraints. This research also highlights opportunities for further studies, especially to explore PII’s role in the network of Islamic proselytization in West Sumatra and its continuity post-2006, to understand the dynamics of Islamic organizations amidst socio-political changes in Indonesia.